Taf’īl al-Anmāṭ at-Tafā‘uliyyah fī Ta’līm al-Lugah al-‘Arabiyyah Dākhila al-Bī`ah al-Iṣṭinā’iyyah ‘alā Ḍau’i an-NaẒariyyah al-Ijtimā‘iyyah aṡ- Ṡaqafiyyah li Vygotsky - Imam Muttaqin; Abdul Wahab Rasyidi (IAIN Salatiga, 2020)
The interaction patterns of Arabic learning can be realized in an artificial environment based on Vygotsky's socio-cultural theory. This research aims; 1. To know the interaction patterns of learning Arabic in an artificial environment. 2. To know how to activate the interaction patterns of learning Arabic in an artificial environment based on Vygotsky's socio-cultural theory. This research is a qualitative analysis descriptive study with a symbolic interactional approach. The data collected by using observation, interviews and documentation. The results of data analysed by using the Miles and Huberman analysis methods. For validating the data used triangulation method. This study finds out that, 1. The pattern of Arabic learning interaction; a. Interaction between teachers students. b. Interaction between teachers groups of students, c. Interaction between teacher groups student groups. 2. There are important thing in activating the interaction pattern; a. Mediated learning. b. Ensure the regulation in children by using scaffolding techniques in zone proximal development of student (ZPD). c. Apply the micro genesis model by providing collaborative learning. d. Watch for and supervise the use of children's